Perumusan Strategi Bisnis pada PT. Integra Kreasitama Solusindo - Krisna Amalia; Toto Hardiyanto; Syahfirin Abdullah (The Graduate School of Sahid University, 2021)
ABSTRACTThis study aims to analyze the audit results of financial performance, ICT and Digital industries, formulate strategies at the company PT. Integra Kreasitama Solusindo and recommend the results of the strategy formulation process. The research method used is qualitative descriptive analysis with case studies of PT. Integra Kreasitama Solusindo is a company that has a business focus on ICT as a system integrator, technology solution, multimedia digital. The data sources used consist of primary data and secondary data. Financial performance analysis results in the last 3 (three) years for sales achievement with a consistent increase of 200%. Based on the results of the analysis of the ICT and Digital industry, PT. Integra Kreasitama Solusindo in competing in this industry is very high competition within similar companies. In formulating strategy at PT. Integra Kreasitama Solusindo in the calculation of the SWOT analysis shows that the company is in Quadrant I, meaning that it is advisable to carry out a strategy that supports an aggressive growth policy. Recommendations from the results of the strategy formulation of PT. Integra Kreasitama Solusindo from the results of the QSPM matrix, namely market penetration and market development. And the penetration strategy can be done by PT. Integra Kreasitama Solusindo with a focus on existing sites, market development to group/chain companies and expansion to potential cities, especially outside Java, and can provide discounts or product/service bundling and add more advertising or product/service packaging interesting.